Schools’ Strengths and Areas for Improvement: Perspectives From External Evaluation Reports - Seabra, Filipa; Henriques, Susana; Mouraz, Ana; Abelha, Marta; Tavares, Ana (Frontiers in Education, 2022)
In the context of schools’ growing autonomy, mechanisms of external evaluation, including External Evaluation of Schools (EES), are increasingly central to educational policies. This article is based on documentary analysis of all the reports of External Evaluation of Schools in Portugal (77 reports), focusing on two sections of those reports – the strengths and areas for improvement they identified. The analysis intends to uncover the areas EES is currently stressing as relevant to assess school’s quality and identify tendencies across years of implementation and territorial areas. The results identify some territorial areas’ impact, highlighting the effects of the agents interpreting and implementing the policies. Some areas are highlighted as critical – such as the impact of self-evaluation, management, curriculum management, supervision and accompaniment of teaching practice, evaluation, pedagogical practices, or the analysis and improvement of results. These areas are aligned with broader educational policy priorities.